The Leadership Role of School Principals in Curriculum Management: Systematic Literature Review Analysis - Nurlaeli, Acep; Ferianto, Ferianto; Makbul, M.; Munafiah, Nida’ul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The role of the principal in curriculum management is critical to ensure effective implementation and alignment with educational standards and objectives. This study aims to determine the role of principals in curriculum management based on a systematic review of the literature using NVivo software. This research uses the SLR method with an inductive approach, and the analysis is carried out using NVivo software. A literature review study using NVivo found that: 1) After screening with inclusion and exclusion criteria, the number of relevant articles was 21. The articles are spread across various journals, with the highest number being four articles in the journal